2014
DOI: 10.1016/j.ejphar.2014.01.021
|View full text |Cite
|
Sign up to set email alerts
|

JM-20, a novel benzodiazepine–dihydropyridine hybrid molecule, protects mitochondria and prevents ischemic insult-mediated neural cell death in vitro

Abstract: The ischemic stroke cascade is composed of several pathophysiological events, providing multiple targets for pharmacological intervention. JM-20 (3-ethoxycarbonyl-2-methyl-4-(2-nitrophenyl)-4,11-dihydro-1H-pyrido[2,3-b][1,5]benzodiazepine) is a novel hybrid molecule, in which a benzodiazepine portion is covalently linked to a dihydropyridine ring, forming a new chemical entity with potential multisite neuroprotective activity. In the present study, JM-20 prevented PC-12 cell death induced either by glutamate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…We observed here that JM-20 enhanced glutamate uptake in astrocyte culture alone at very low micromolar concentrations, but it did not, in cortical neurons. Because the astrocytic glutamate transport plays a major role in maintaining extracellular glutamate concentrations below neurotoxic levels (Anderson and Swanson, 2000;Danbolt, 2001), and the neurotransmitter uptake by astrocytes can be stimulated by several neuroprotective compounds (Beller et al, 2011;Karki et al, 2014;Wu et al, 2008), the above mentioned effects of JM-20 may contribute to explain its anti-excitotoxic actions in vitro (Nuñez-Figueredo et al, 2014a) and in vivo (Nuñez-Figueredo et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We observed here that JM-20 enhanced glutamate uptake in astrocyte culture alone at very low micromolar concentrations, but it did not, in cortical neurons. Because the astrocytic glutamate transport plays a major role in maintaining extracellular glutamate concentrations below neurotoxic levels (Anderson and Swanson, 2000;Danbolt, 2001), and the neurotransmitter uptake by astrocytes can be stimulated by several neuroprotective compounds (Beller et al, 2011;Karki et al, 2014;Wu et al, 2008), the above mentioned effects of JM-20 may contribute to explain its anti-excitotoxic actions in vitro (Nuñez-Figueredo et al, 2014a) and in vivo (Nuñez-Figueredo et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we showed that JM-20 inhibits the hydrolytic activity of F1FO-ATP synthase in mitochondria and submitochondrial particles isolated from rat liver (Nuñez-Figueredo et al, 2014a). Considering that F-ATPases and V-ATPases have structural and functional similarities, we hypothesized that this molecule may inhibit V-ATPase activity.…”
Section: Jm-20 Specifically Inhibits Bafilomycin-sensitive H + -Atpasmentioning
confidence: 95%
See 2 more Smart Citations
“…After MTT withdrawal, 200 µl of DMSO was added to each well to solubilize the formazan crystals, and the absorbance of each well was measured at 540 nm using a microplate reader (POLARstar Omega fluorescence spectrophotometer, Germany). The results are expressed as the percentage of absorbance relative to the undamaged control cells [15].…”
Section: Pc-12 Cell Viability Assaysmentioning
confidence: 99%